2021
DOI: 10.1386/hosp_00044_1
|View full text |Cite
|
Sign up to set email alerts
|

Hospitality & Society: Critical reflections on the theorizing of hospitality

Abstract: This article is the second part of a critical reflection upon the progress of Hospitality & Society in its first ten years. Analysis of the articles published highlights conceptual contributions made to the field of hospitality studies. Thirteen major themes are identified: conceptualizations of hospitality; migration and labour; lifestyle; social hospitality; hospitality, consumption, global citizenship and ethics; addressing neglected areas of research; hostipitality, violence and exploitation; hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 159 publications
0
5
0
1
Order By: Relevance
“…Thus, hospitality simultaneously shapes and is shaped by the world in which it exists, a notion that expands the scope of its research and practice. In this regard, the HOST framework echoes Lynch et al (2021), who suggested:…”
Section: Ijchm 367mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, hospitality simultaneously shapes and is shaped by the world in which it exists, a notion that expands the scope of its research and practice. In this regard, the HOST framework echoes Lynch et al (2021), who suggested:…”
Section: Ijchm 367mentioning
confidence: 99%
“…This “impairs pedagogical integrity, thus, affecting the ability to establish the epistemological roots of the new and emerging hospitality discipline” (Ottenbacher et al , 2009, p. 263). Accordingly, there is a pressing need to reimagine and re-establish the role, scope and possibilities of hospitality research, education and practice; however, this requires a perspective that incorporates both the study of hospitality as a focus of inquiry and also hospitality as an analytical device of social analysis that “allows one to deconstruct the topic of investigation from a hospitality perspective prior to reflection upon its broader significance” (Lynch et al , 2021). The present study attempts to fill this gap by offering a conceptual framework that reimagines the role of hospitality in society.…”
Section: Conceptualizations Of Hospitalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of hospitality is crucial for understanding the sites and practices of touristic destinations. On the one hand, it does refer to the provision of goods, services and experiences for the guests, while on the other hand, it is a constitutive part of the identity and image of any receptive structure (Lynch et al, 2021). Moreover, hospitality identifies a common ground between hosts and guests that allows their encounter and the establishment of a relationship, as is revealed by the Latin origin of the term (hospes, a word used to indicate both host and guest).…”
Section: Introductionmentioning
confidence: 99%
“…Дослідники Лінч П., Макінтош Дж. А., Лугосі Р. у статті «Гостинність і суспільство: Критичні роздуми про теоретизацію гостинності» [9] аналізують концептуальний внесок у сферу досліджень гостинності на основі публікацій, в яких визначено 13 основних тем: концептуалізація гостинності; міграція та праця; спосіб життя; соціальна гостинність; гостинність, споживання, глобальне громадянство та етика; звернення до забутих сфер досліджень; ворожість, насильство та експлуатація; кар'єра в сфері гостинності та вища освіта; історичні дослідження; імідж та ідентичність; простір, дизайн і їжа; менеджмент гостинності та неолібералізм; гостинність і технології [9].…”
unclassified